Acquired Asymptomatic Blue Tongue: A Report of Exogenous Agent-associated Tongue Dyschromia and Review of Blue Tongue Etiologies - Cohen, Philip R (Cureus, 2019)
This study presents the case of a man who developed a temporary and asymptomatic blue tongue. The dyschromia occurred following topical contact with gelato that contained Food, Drug, and Cosmetic (FD&C) blue dye no. 1. The etiology of a blue tongue is either congenital (in individuals with blue rubber bleb nevus syndrome) or acquired. Acquired blue dyschromia of the tongue results from either endogenous conditions or exogenous agents. The endogenous conditions include not only benign (angioleiomyoma, hemangioma, melanocytic macule, and varicosities) and malignant (ovarian carcinoma) tumors but also reactive lesions (intravascular papillary endothelial hyperplasia and mucocele) and systemic disorders (argyria, cyanosis, methemoglobinemia, primary adrenal insufficiency, and thrombocytosis). Exposure to the exogenous agents can either be systemic (ingestion of medications such as haloperidol, metoclopramide, minocycline, prochlorperazine, and risperidone), traumatic (tattoo resulting from the implantation of dental amalgam), or topical (contact with FD&C blue dye no. 1). Clinical clues to the topical exogenous etiology in the reported individual included not only the fact that the dyschromia spared both the lateral aspects and the tip of the tongue but also the observation that the blue color focally appeared on his upper lip.